2022
DOI: 10.1186/s12957-022-02776-y
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigens and their clinical applications in human gastrointestinal cancers

Abstract: Background Tumor-specific neoantigens are ideal targets for cancer immunotherapy. As research findings have proved, neoantigen-specific T cell activity is immunotherapy’s most important determinant. Main text There is sufficient evidence showing the role of neoantigens in clinically successful immunotherapy, providing a justification for targeting. Because of the significance of the pre-existing anti-tumor immune response for the immune checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 203 publications
0
3
0
Order By: Relevance
“…A peptide MHC class I molecule IgG-antibody fusion protein-redirected vaccine was demonstrated to target lung cancer cells in vivo and endow them with viral antigenicity, thereby activating antiviral CD8 + T cells induced by the vaccine and inhibiting tumor growth (122). Tumor vaccines are designed to target tumor neoantigens as a part of MHC molecule-binding neoantigen immunotherapy (123). Duperret et al (124) used DNA vaccines to target tumor neoantigens for preclinical research and found that the optimized tumor neoantigens were immunogenic and mainly produced MHC I molecule-restricted CD8 + T-cell responses.…”
Section: Clinical Significance Of Hla In Tumor Immunotherapymentioning
confidence: 99%
“…A peptide MHC class I molecule IgG-antibody fusion protein-redirected vaccine was demonstrated to target lung cancer cells in vivo and endow them with viral antigenicity, thereby activating antiviral CD8 + T cells induced by the vaccine and inhibiting tumor growth (122). Tumor vaccines are designed to target tumor neoantigens as a part of MHC molecule-binding neoantigen immunotherapy (123). Duperret et al (124) used DNA vaccines to target tumor neoantigens for preclinical research and found that the optimized tumor neoantigens were immunogenic and mainly produced MHC I molecule-restricted CD8 + T-cell responses.…”
Section: Clinical Significance Of Hla In Tumor Immunotherapymentioning
confidence: 99%
“…For instance, TMB frequency varies in different tumour types and densities levels of CD8+ and increased CD4+/CD8+ ratios in pre-treatment secondary PDAC specimens than in primary tumour tissue samples. PDAC has a tendency of decreased number of somatic mutations which may be an explanation of their low immunogenicity and ICI responses [222] . About 81% out of over 4000 PDAC tumour samples showed KRAS mutation, and they also showed increased infiltration of cancer-associated fibroblasts and M1 macrophages, decreased ratio of CD4+/CD8+, and MSI-H status.…”
Section: Immunotherapy Combined With Other Therapy Formsmentioning
confidence: 99%
“…In recent times, immunotherapy has manifested marked advantages and efficacy in treating malignancies, in addition to conventional therapies like surgery, radiation, chemotherapy, and targeted therapy. Presently, the most commonly employed immunotherapeutic agents primarily comprise checkpoint inhibitor monoclonal antibodies directed against programmed cell death 1 (PD-1) or its ligand, PD-L1, and chimeric antigen receptor T-cell (CAR-T) therapies, with other agents currently undergoing clinical trials 2 . Despite the significant advancements in immunotherapy, its effectiveness and safety remain subject to reservations, thereby limiting its clinical utility in treating certain GI tumors 3 , such as PDAC.…”
Section: Introductionmentioning
confidence: 99%